1991
DOI: 10.1056/nejm199110033251403
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal Nocturnal Hemoglobinuria with Onset in Childhood and Adolescence

Abstract: Children and adolescents with PNH have a greater prevalence of bone marrow failure than do adults with this disorder, and their morbidity and mortality are high. Bone marrow transplantation should be considered for selected young patients with PNH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
102
3
10

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(124 citation statements)
references
References 33 publications
7
102
3
10
Order By: Relevance
“…There are many international studies which have shown variable incidence of PNH with aplastic anemia. [15,16] There are only occasional case reports from our country; [17,18] and therefore, it was not possible to compare the incidence with Indian studies.…”
Section: Discussionmentioning
confidence: 99%
“…There are many international studies which have shown variable incidence of PNH with aplastic anemia. [15,16] There are only occasional case reports from our country; [17,18] and therefore, it was not possible to compare the incidence with Indian studies.…”
Section: Discussionmentioning
confidence: 99%
“…As the confirmatory tests for PNH were positive in all, this delay can be attributed to lack of awareness and varied presentations. The classical nocturnal hemoglobinuria is present in only a minority of patients (2] and the diagnosis may be missed for months or years (1,3]. In most cases haemoglobinuria is irregular and transient.…”
Section: Discussionmentioning
confidence: 99%
“…Около 10 % случаев заболевания приходится на ПНГ в детском и подростковом возрасте [1,[3][4][5][6][7]. У детей ПНГ чаще встречается в сочетании с синдро-мом костномозговой недостаточности, а яркий при-знак ПНГ -гемоглобинурия -отмечается примерно в 15 % случаев [3].…”
unclassified
“…К л и н и ч е с к и е н а б л ю д е н и я Выводы ПНГ встречается у детей и подростков (примерно 10 % пациентов с ПНГ младше 21 года), но очень часто заболевание не диагностируется вовремя и пациенты долгое время не получают адекватного лечения [3][4][5][6][7]. Так, в приведенном клиническом наблюдении диагноз ПНГ был впервые поставлен через 4 года от момента первой госпитализации и через 6 лет от дебюта заболе-вания.…”
unclassified